MiT family translocation renal cell carcinoma with retroperitoneal metastasis in childhood: a case report - Yang, Kaihang; Ma, Yuhao; Dai, Shuyang; Dong, Rui (Frontiers in Pediatrics, 2023)
RCC accounts for only 0.1%–0.3% of all kidney tumors and 2%–6% of malignant kidney tumors in children. Accounting for approximately one-third of the total number of cases in children and adolescents with RCC, Xp11.2 tRCC is the most common subtype of the MiT family translocation renal cell carcinoma, which is a group of rare childhood and adult tumors, characterized by recurrent gene rearrangements of TFE3. Here we report a rare case of a 6-year-old male patient with MiT family translocation renal cell carcinoma (MiTF tRCC) where the patient developed retroperitoneal metastasis. The patient underwent partial nephrectomy (PN), radical nephrectomy (RN), abdominal lymph node resection, and intestinal adhesion lysis. Microscopically, we detected focal and nest clump-shaped clusters of tumor cells whose cytoplasm was bright and clear. Immunohistochemistry (IHC) showed tumor cells diffusely expressed TFE3, and fluorescence in situ hybridization (FISH) demonstrated disruption of the TFE3 locus, confirming the diagnosis of Xp11.2 tRCC, the most common subtype of MiTF tRCC. Eventually, the patient obtained a good therapeutic result. This case can provide a good reference and guidance for pediatric urologists and oncologists to recognize and diagnose rare renal cell carcinoma in children.